Bulk-tuned Gm–C filter using current cancellation. Issue 8 (August 2015) - Moreno, Ricardo F.L.; Barúqui, Fernando A.P.; Petraglia, Antonio
Abstract A new approach for small transconductance (Gm) OTA designs, suitable for relatively low frequency filtering applications in the range of few kHz, is proposed. Small Gm values are achieved by a current cancellation technique, and are adjustable by bulk driving the MOS transistors of the input differential amplifier. The OTA design procedure takes into account Pelgrom׳s modeling of mismatch errors. A common-mode feedback control circuit based on floating gate common-mode voltage detector that shares the filter main capacitances is also presented. Experimental results obtained with a low-pass filter with tunable cutoff frequency implemented in a 0.35 μm CMOS process to verify the effectiveness of the design procedure have shown close agreement with the theory.